A study of the spray characteristic for valve covered orifice diesel nozzle injector using CFD - Ahmad Aizuddin Faiz, Che Jaafar (2013)
Diesel engine performance and emissions are strongly coupled with fuel atomization and spray processes, which in turn are strongly influenced by injector flow dynamics. Modern engines employ micro-orifice with different orifice designs. It is critical to characterize the effects of various designs on engine performance and emissions. Spray characteristic of diesel fuel injection is one of the most important factors in diesel combustion and pollutant emissions where the interval between the onset of combustion and the evaporation of atomized fuel is relatively short. Therefore, this project is to study the spray simulation of diesel fuel using valve covered orifice (VCO) nozzle injector in the closed chamber. Three main components are focused on this paper, first is the relation between the spray characteristic influences of the various ambient temperature,. The second focus is the influences of the injection pressure,to the spray characteristic and the third focus is relation between the various diameter of nozzle hole size to the spray characteristic. Good spray characteristic leads to the good drivability, high combustion efficiency and stoichiometric air-fuel mixture. Therefore,Computational Fluid Dynamics (CFD) method using ANSYS Fluent simulation software is used for this purpose. The simulation of injection spray in chamber is conducted by using diesel fuel with the single and double-hole Valve Covered Orifice (VCO) nozzle, injection pressure, were various in range 5 KPa – 150 MPa, the ambient pressure, at atmosphere pressure at 101.325 Pa, the ambient temperature,was various in range of 273 K – 1000 K and at the same time iteration.